2000
DOI: 10.1063/1.1333401
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution transmission electron microscopy study of epitaxial oxide shell on nanoparticles of iron

Abstract: Remarkably oxidation-resistant nanoparticles of iron prepared at Tianjin University have been studied by electron diffraction and high-resolution transmission electron microscopy (HRTEM). HRTEM images clearly show the polyhedral epitaxy of γ-Fe2O3 layers on equivalent {100} facets of the {100} truncated {110} rhombic dodecahedral nanoparticles of iron. Oxide layers on {110} facets are formed by the lateral extension of the epitaxial {100} γ-Fe2O3 layers over adjacent {110} facets. The {110} oxide layers are be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…The size of these particles ranged from tens of nanometers to about 500 nm. Transmission electron microscope (TEM) observations found that all these particles have a thin oxidation layer of 4 nm in thickness, regardless of the particle size, exactly the same as that reported before [26,27]. This suggests that these particles are stable in ambient environment.…”
Section: Submitted Tosupporting
confidence: 84%
See 1 more Smart Citation
“…The size of these particles ranged from tens of nanometers to about 500 nm. Transmission electron microscope (TEM) observations found that all these particles have a thin oxidation layer of 4 nm in thickness, regardless of the particle size, exactly the same as that reported before [26,27]. This suggests that these particles are stable in ambient environment.…”
Section: Submitted Tosupporting
confidence: 84%
“…These nanoparticles were synthesized by argon plasma evaporation of an iron target, and then passivated in a connecting chamber in an inert gas ambient [26,27]. The size of these particles ranged from tens of nanometers to about 500 nm.…”
Section: Submitted Tomentioning
confidence: 99%
“…This suggests that, in agreement with the CM theory, growth of oxide stops after reaching certain limiting thickness. In the case of iron nanoparticles also, prepared by the gas condensation technique, the oxide shell shows a remarkable resistance to further oxidation of metal core [36].…”
Section: Resultsmentioning
confidence: 99%
“…In Fe or Co nanoparticles [35][36][37][38] and the sidewalls of Co-Fe-B-based magnetic tunnel junctions [38], there is a thin layer of oxide, which is polycrystalline and has randomly oriented grains. Unfortunately, the shell thickness could not be determined directly for these nanodots, but in similar structures the thickness is estimated to be [40]. Just as ferromagnetic cobalt ferrite has a much larger anisotropy than Co-Fe, the surface oxide here, Co-Fe-B-O x , is likely to be ferrimagnetic and of higher anisotropy than Co-Fe-B.…”
Section: Resultsmentioning
confidence: 99%